2020
DOI: 10.1093/cid/ciaa1268
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics and Outcomes of 11 721 Patients With Coronavirus Disease 2019 (COVID-19) Hospitalized Across the United States

Abstract: BACKGROUND As COVID-19 disseminates throughout the US, a better understanding of patient characteristics associated with hospitalization, morbidity and mortality in diverse geographic regions is essential. METHODS Hospital chargemaster data on adult patients with COVID-19 admitted to 245 hospitals across 38 states between February 15 and April 20, 2020 were assessed. Clinical course from admission through hospitalization to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
100
5
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(128 citation statements)
references
References 26 publications
15
100
5
8
Order By: Relevance
“…There was not a significant difference among the genders regarding mortality (p=0.6553). The male patient ratio is consistent with the US data [ 13 ]. In a study conducted in Iran, Raoufi et al reported no difference between genders in terms of mortality among 380 COVID-19 patients [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There was not a significant difference among the genders regarding mortality (p=0.6553). The male patient ratio is consistent with the US data [ 13 ]. In a study conducted in Iran, Raoufi et al reported no difference between genders in terms of mortality among 380 COVID-19 patients [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…Median LOS was significantly longer in non-survivors than in survivors (13.0 vs. 8.0, p=0.0251). US data revealed median LOS of 7.0 [ 13 ]. Pan et al reported longer median LOS in survivors than in non-survivors, with no significant difference (14.0 vs. 18.0, p=0.068) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, 315 records were excluded with reasons, including studies that were in-vitro/in-silico/animal experiments (n=96), investigating other medications (n=93), evaluating other diseases (n=68), review/systematic review and meta-analysis/editorial/commentary (n=18), irrelevant (n=17), unfinished/terminated/suspended clinical trials (n=13), duplicates (n=8), or case reports (n=2). Finally, ten studies, including five RCTs ( Beigel et al, 2020b ; Goldman et al, 2020 ; Pan et al, 2020 ; Spinner et al, 2020 ; Wang et al, 2020 ) and five NRSIs ( Antinori et al, 2020 ; Fried et al, 2020 ; Grein et al, 2020 ; Olender et al, 2020 ; Pasquini et al, 2020 ), were entered into the meta-analysis ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of our patients admitted to ICU received mechanical ventilation. The reported crude mortality of previous reports in the same population was 70% [7] , [8] , [9] . In our cohort, the in-hospital absolute mortality rate in those cases admitted to ICU was lower (48·98%).…”
mentioning
confidence: 66%